Surprised or not surprised? The investors’ reaction to the comprehensive assessment preceding the launch of the banking union - Carboni, Marika; Fiordelisi, Franco; Ricci, Ornella; Lopes, Francesco Saverio Stentella (Journal of Banking & Finance, 2017)
Did the Comprehensive Assessment (CA), preceding the Single Supervisory Mechanism (SSM) launch in Europe, achieve its aims of producing new valuable information for the market? We show that the CA achieved the goal of increasing transparency: investors were able to detect weak banks at the announcement of the procedure (23rd October 2013), but gained full information on the amount of the capital shortfall only at the disclosure of the results (26th October 2014). Furthermore, at the official launch of the SSM (4th November 2014), banks under direct European Central Bank (ECB) supervision registered a more negative market reaction with respect to banks maintaining their national supervisors. Using a regression model including possible confounders and allowing for treatment effect heterogeneity, this negative reaction is confirmed. These findings suggest that, at least in the short run, investors penalized banks subject to direct ECB supervision, probably because of the fear of regulatory inconsistencies.